Engineering of service-oriented automation systems: a survey - Mendes, João M. (2008)
The evolution of manufacturing systems and the emergence of decentralised control require flexibility at various levels of their lifecycle. New emerging methods, such as multi-agent and service-oriented systems are major research topics in the sense of revitalizing the traditional production procedures. This paper takes an overview of the serviceoriented approach in terms of platform and engineering tools, from the perspective of automation and production systems. From the basic foundation to the more complex interactions, service-oriented architectures and its implementation in form of web services provide diverse and quality proved features that are welcome to different states of the production systems’ life-cycle. Key elements are the concepts of modelling and collaboration, which enhance the automatic binding and synchronisation of individual low-value services to more complex and meaningful structures. Such interactions can be specified by Petri nets, a mathematically well founded tool with features that enhance towards the modelling of systems. The right application of different methodologies together should motivate the development of service-oriented manufacturing systems that embrace the vision of collaborative automation.